Formulation and Evaluation of Sustained Release Tablet of Metformin Hcl and Glimepride - Patel, Arun (International Journal of Pharmaceutical & Biological Archive, 2016)
Formulation and Evaluation of Sustained Release Tablet of Metformin Hcl and Glimepride